The effect of acute dark chocolate consumption on carbohydrate metabolism and performance during rest and exercise - Stellingwerff, T.; Godin, J. -P.; Chou, C. J.; Grathwohl, D.; Ross, A. B.; Cooper, K. A.; Williamson, G.; Lucas Actis-Goretta, L. (Applied Physiology, Nutrition, and Metabolism, 2014)
Consumption of cocoa-enriched dark chocolate (DC) has been shown to alter glucose and insulin concentration during rest and exercise compared with cocoa-depleted control (CON). However, the impact of DC consumption on exercise metabolism and performance is uncertain. Therefore, we investigated carbohydrate metabolism via stable isotope tracer techniques during exercise after subjects ingested either DC or CON. Sixteen overnight-fasted male cyclists performed a single-blinded, randomized, crossover design trial, after consuming either DC or CON at 2 h prior to 2.5 h of steady-state (SS) exercise (45% peak oxygen uptake). This was followed by an 15-min time-trial (TT) and 60 min of recovery. [6,6-2H2]Glucose and [U-13C]glucose were infused during SS to assess glucose rate of appearance (Ra) and disappearance (Rd). After DC consumption, plasma (-)-glucose and insulin concentrations were significantly (p < 0.001) elevated throughout vs. CON. During SS, there was no difference in [6,6-2H2]glucose Ra between treatments, but towards the end of SS (last 60 min) there was a 16% decrease in Rd in DC vs. CON (p < 0.05). Accordingly, after DC there was an 18% significant decrease in plasma glucose oxidation (trial effect; p = 0.032), and an 15% increase in tracer-derived muscle glycogen utilization (p = 0.045) late during SS exercise. The higher blood glucose concentrations during exercise and recovery after DC consumption coincided with high concentrations of epicatechin and (or) theobromine. In summary, DC consumption altered muscle carbohydrate partitioning, between muscle glucose uptake and glycogen oxidation, but did not effect cycling TT performance.